التنظيم القانوني للحق في الإضراب - حويشي قادة صيدون علي (جامعة المسيلة, 2024)
The issue of the legal regulation of the right to strike is one of the most problematic legal and practical issues, both in the past and in the present times, and this is what prompted the Algerian legislator to issue legal texts to regulate the right to strike. The aim of the study of this research is to clarify the various provisions related to the strike, starting the research with the definition of the right to strike, the conditions for its exercise, and the various legal procedures to be followed in order to exercise it within the framework that the legislator has singled out and enshrined in the labor legislative system, and the research also includes exposure to the system of settling the exercise of this right by studying the preventive measures of the strike and ways to settle it in a way that ensures the balance of interests, workers and the body used.
Keywords: régulation; Law; Strike; right.